Inorganic Double Helices in Semiconducting SnIP. Issue 44 (14th September 2016) - Pfister, Daniela; Schäfer, Konrad; Ott, Claudia; Gerke, Birgit; Pöttgen, Rainer; Janka, Oliver; Baumgartner, Maximilian; Efimova, Anastasia; Hohmann, Andrea; Schmidt, Peer; Venkatachalam, Sabarinathan; van Wüllen, Leo; et al.
Abstract : SnIP is the first atomic‐scale double helical semiconductor featuring a 1.86 eV bandgap, high structural and mechanical flexibility, and reasonable thermal stability up to 600 K. It is accessible on a gram scale and consists of a racemic mixture of right‐ and left‐handed double helices composed by [SnI] and [P] helices. SnIP nanorods <20 nm in diameter can be accessed mechanically and chemically within minutes.